2007 IEEE International Geoscience and Remote Sensing Symposium 2007
DOI: 10.1109/igarss.2007.4423689
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric analysis of maritime SAR data collected with the DSTO ingara X-Band radar

Abstract: Fine resolution spotlight synthetic aperture radar (SAR) imagery collected on a circular flight path is used to investigate the variation in ship detection performance with respect to three fundamental radar parameters: the transmit/receive polarisation combination, the incidence angle and the azimuth angle. The polarisation combinations examined are HH, HV, VV, RR and cross-slant 45 • . Three different incidence angles are considered -50 • , 60 • and 70 • -corresponding to collection geometries for high altit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…These plots, like the others below have been edited to remove bad data points caused by saturation of the ADCs in the radar receiver. The ocean results are as expected and conform to know trends [4]. Note though that the cross wind trough at azimuth angle 290 • is significantly deeper that at 100 • .…”
Section: Co-variance Matrix Variation With Azimuthsupporting
confidence: 84%
“…These plots, like the others below have been edited to remove bad data points caused by saturation of the ADCs in the radar receiver. The ocean results are as expected and conform to know trends [4]. Note though that the cross wind trough at azimuth angle 290 • is significantly deeper that at 100 • .…”
Section: Co-variance Matrix Variation With Azimuthsupporting
confidence: 84%
“…Other studies [6,7,39,40] have looked at characterising the polarimetric signature of high grazing angle sea-clutter using the Cloude-Pottier 'entropy-alpha' decomposition. Quantitative analysis of a wooden fishing vessel [40] indicated that the HH is the best polarisation for detecting targets.…”
Section: Doppler Spectramentioning
confidence: 99%
“…This radar has been deployed in a number of trials, and subsequent analysis of the resultant clutter and detection performance has been documented extensively [25][26][27][28].…”
Section: Ingara Radar and Cluttermentioning
confidence: 99%